2014
DOI: 10.3390/molecules20010358
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Symplocos racemosa

Abstract: (1), was isolated from the aerial parts of Symplocos racemosa along with 15 known flavonoids (2-16). Their structures were characterized by Q-TOF mass, optical rotation, UV, 1D and 2D-NMR spectroscopic data. Compounds 3, 9, 16 showed moderate inhibitory activities against NO production with IC50 value of 88.2, 42.1 and 74.3 μM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…As part of our ongoing search to discover anti-inflammatory agents from medicinal plants, 14,15) Sophora tonkinensis was selected due to previous reports related to the modulation of inflammatory responses. [16][17][18] Currently, the proprietary extract from S. tonkinensis is under clinical trials in the Republic of Korea for the treatment of asthma.…”
mentioning
confidence: 99%
“…As part of our ongoing search to discover anti-inflammatory agents from medicinal plants, 14,15) Sophora tonkinensis was selected due to previous reports related to the modulation of inflammatory responses. [16][17][18] Currently, the proprietary extract from S. tonkinensis is under clinical trials in the Republic of Korea for the treatment of asthma.…”
mentioning
confidence: 99%
“…As part of our ongoing search to discover anti-inflammatory agents from medicinal plants [12,13], 6,8-diprenyl-7,4 -dihydroxyflavanone (DDF) was newly isolated from the roots of Sophora tonkinensis. Seven flavanones were isolated as chemical constituents from the roots of Sophora tonkinensis previously, Effects of eight flavanones on the viability of RAW 264.7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Data represent the mean ± SEM of three experiments. * Significant difference from Nor, p < 0.05. and these compounds were used in the present study [12]. Flavanones from Sophora tonkinensis were tested for their inhibitory activity against nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells, since previous studies reported on the modulation of inflammatory cytokines [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on spectroscopic data and by comparison to previously reported compounds, Compounds 3 – 37 were identified as: scopoletin ( 3 ) [18], naringenin ( 4 ) [19], p -hydroxybenzoic acid ( 5 ) [20], pyrogallol ( 6 ) [21], protocatechuic acid ( 7 ) [22], taxifolin ( 8 ) [23], aromadendrin ( 9 ) [24], eriodictyol ( 10 ) [25], mearnsetin ( 11 ) [26], luteolin ( 12 ) [27], fraxetin ( 13 ) [28], naringenin 5- O -β- d -glucopyranoside ( 14 ) [29], methyl 4-hydroxylbenzoate ( 15 ) [30], (−)-salipurposide ( 16 ) [31], naringenin 4′- O -β- d -glucopyranoside ( 17 ) [32], (+)-catechin ( 18 ) [33], epicatechin ( 19 ) [34], quercetin ( 20 ) [34], eriodictyol 4′- O -β- d -glucopyranoside ( 21 ) [35], tricetin ( 22 ) [36], (2 S )-eriodictyol 7- O -β- d -glucopyranoside ( 23 ) [37], (2 R )-eriodictyol 7- O -β-glucopyranoside ( 24 ) [38], gallic acid ( 25 ) [39], gallocatechin ( 26 ) [40], kaempferol 3- O -rutinoside ( 27 ) [41], isorhamnetin 3- O -rutinoside ( 28 ) [42], isoquercitrin ( 29 ) [43], quercitrin ( 30 ) [44], 2α,3α-epoxy-5,7,3′,4′-tetrahydroxyflavan-(4β-8-catechin) ( 31 ) [45], proanthocyanidin A2 ( 32 ) [46], isomericitrin ( 33 ) [47], quercimetrin ( 34 ) [48], rutin ( 35 ) [34], myricetrin ( 36 ) [44], and myricetin 3- O -rutinoside ( 37 ) [49].…”
Section: Resultsmentioning
confidence: 99%